Product Improvement with Quality Function Deployment (QFD) Technique - (:unkn) unknown (TRANS TECH PUBLICATIONS LTD, 2012)
The purpose of this paper is to improve a new part for the natural gas sector using Quality Function Deployment (QFD) technique. QFD methodology was chosen for the product improvement process at IGDAS (Istanbul natural gas distribution company), the biggest natural gas distribution firm in Turkey. Experts from engineers were selected to determine customer expectations. Application of QFD to pipe strangling equipment is described step by step. The results show that when developing a new product or improving a product both customer expectations and product requirements are evaluated at the same time pleasing both parties for a successful result.
Keywords: QFD; quality; new product development; customer expectation